Complementarity between solar and hydro power: Sensitivity study to climate characteristics in Northern-Italy. (February 2016) - François, B.; Borga, M.; Creutin, J.D.; Hingray, B.; Raynaud, D.; Sauterleute, J.F.
Abstract: Climate related energy sources such as wind, solar and runoff sources are variable in time and space, following their driving weather variables. High penetration of such energy sources might be facilitated by using their complementarity in order to increase the balance between energy load and generation. This study presents the analysis of the effect of a 100% renewable energy mix composed by solar and run-of-the-river energy in Northern Italy where these two energy sources are the main alternative energy sources. Along a climate gradient from the Alpine crest (snow melt dominated area) to the Veneto plain (rainfall dominated area), solar power is generated in the flat plain, and run-of-the-river hydropower at two mountainous locations. Covering all possible mixes of these two sources, we analyze their complementarity across different temporal scales using two indicators: the standard deviation of the energy balance and the theoretical storage required for balancing generation and load. Results show that at small temporal scale (hourly), a high share of run-of-the-river power allows minimizing the energy balance variability. The opposite is obtained at larger temporal scales (daily and monthly) essentially because of lower variability of solar power generation, which also implies a lower storage requirement. Highlights: Soar photovoltaic (PV) and run-of-the-river power (RoR) from different hydrological regime area are combined in order to smooth the energy balance in Northern Italy. The optimal share among solar PV and RoR coming from either Alpine area or rain-fed catchment depends on the time scale. At small scale, high share of RoR minimizes the energy balance because of high variability of solar PV. At larger time scales, high share of PV minimizes the energy balance and implies a lower storage requirement.